4z-6=5z-2

Simple and best practice solution for 4z-6=5z-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4z-6=5z-2 equation:


Simplifying
4z + -6 = 5z + -2

Reorder the terms:
-6 + 4z = 5z + -2

Reorder the terms:
-6 + 4z = -2 + 5z

Solving
-6 + 4z = -2 + 5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5z' to each side of the equation.
-6 + 4z + -5z = -2 + 5z + -5z

Combine like terms: 4z + -5z = -1z
-6 + -1z = -2 + 5z + -5z

Combine like terms: 5z + -5z = 0
-6 + -1z = -2 + 0
-6 + -1z = -2

Add '6' to each side of the equation.
-6 + 6 + -1z = -2 + 6

Combine like terms: -6 + 6 = 0
0 + -1z = -2 + 6
-1z = -2 + 6

Combine like terms: -2 + 6 = 4
-1z = 4

Divide each side by '-1'.
z = -4

Simplifying
z = -4

See similar equations:

| 25x+15=24x-2 | | -5(y-5)=6-4y | | 9x-8x=-3 | | x^2-23x-3=0 | | -24t+40=6t-12 | | 2y/7-7/8=9/56 | | 9x-4=4(x+1) | | 3(x+4)+2= | | -4(6n-5)+2n=0 | | (7p+6)(7p-6)=0 | | 34(x-3)=0 | | 2.1a+3=4.1a-2 | | 3x^2+3y^2+18x+6y=0 | | 4x+2y=2.30 | | 6y^2-2y-20= | | (4/3(3/7) | | 8x-15=30+2x | | 10(z+1)-2(z-4)=4(z-4)+3(z-2) | | 6(x+7)-25=0 | | 111=7(1+5x)-1 | | 9c=8 | | 21(2y+1)=0 | | [x-7]x[x-4]=0 | | 6(r+6)=6(r+8) | | 6z=2.5 | | 3(3r-5)=-87 | | 0.6m+1.4+0.04m=14.2 | | 3(7x-3)+4(13-3x)-4(2x+5)=-5 | | 3x^2+84x+153=0 | | 4-2y-y=1y | | 7+4(5x-5)=5-4(2x+1) | | 0.1x^2+0.7x=3 |

Equations solver categories